A STUDY OF THE IMPLEMENTATION OF PROCESS SKILLS AT ELEMENTARY SCHOOLS IN WRINGINANOM-GRESIK - Mia Alifya Djuliyanti; Muhammad Thamrin Hidayat; Akhwani; Nafiah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to reveal the implementation of process skills in the learning process at several Elementary Schools in Wringinanom-Gresik. The method in this study was descriptive qualitative research. The data were collected through a closed questionnaire using a Likert scale with 4 choices, namely SA (Strongly Agree), A (Agree), D (Disagree), SD (Strongly Disagree). The respondents in this study were 21 teachers from several elementary schools. Based on the results obtained from the respondents, it was found that 81% of the teachers agreed and applied the process skills while 18% of the respondents disagreed. This was because not all learning models were applicable by using process skills. This study concluded that the majority of teachers at Elementary Schools in Wringinanom-Gresik implemented and agreed with the learning process using process skills. In addition, it was also found that the teachers’ knowledge about the process skills was good.